Developmental Coordination Disorder: The Importance of Grounded Assessments and Interventions - Niklasson, Mats; Rasmussen, Peder; Niklasson, Irene; Norlander, Torsten (Frontiers in Psychology, 2018)
This focused review is based on earlier studies which have shown that both children and adults diagnosed as having developmental coordination disorder (DCD), benefited from sensorimotor therapy according to the method Retraining for Balance (RB). Different approaches and assessments for children and adults in regard to DCD are scrutinized and discussed in comparison to RB which mainly includes (a) vestibular assessment and stimulation (b) assessment and integration of aberrant primary reflexes and (c) assessment and stimulation of auditory and visual perception. Earlier results indicate that the process of sensorimotor therapy using RB techniques could be described according to a conceptual Kinesthetic-Vestibular Developmental Model (KVDM) whereby the training elicited temporary physical and psychological regressions followed by transformations i.e. positive physical and psychological development. We have also seen that this recurring pattern is similar for children and adults. In our conceptual model vestibular stimulation (perceptual priming) stimulates the nervous system, which might enhance object-related priming. This perceptual priming will also assist the suppression of persistent aberrant primary reflexes. In order to develop effective methods for assessment and intervention of DCD over the life span the importance of primary reflex inhibition and vestibular stimulation as well as a combination of bottom-up and top-down approaches have to be considered.